0261 Pre-Sleep Arousal Predicts Subsequent Night's REM Frontal Theta Power in a Naturalistic Context. (25th May 2022) - ten Brink, Maia; Yan, Yan; Zhang, Jinxiao; Manber, Rachel; Kreibig, Sylvia; Gross, James
Abstract: Introduction: Decreased rapid eye movement (REM) frontal theta spectral activity during sleep has been identified following intense negative experiences in both naturalistic and experimental settings. It is unknown, however, whether this spectral marker a) also appears following lower intensity naturalistic negative affective experiences, and b) whether it is responsive to arousal, to negative valence, or to both. Methods: In a community sample of adults (N = 50, age range 21-49 [M = 30.30, SD = 7.85]) with no mental health or sleep disorders except bruxism, we separately measured naturalistic experiences of negative valence and arousal 40-60 minutes prior to bedtime, then assessed at-home sleep using a single night of ambulatory polysomnography with 8 electroencephalography channels. REM frontal theta was calculated as the mean relative spectral power density between 4.9-8 Hz at F3 and F4 during REM. Affective experience was assessed with a 0-100 slider rating filled out on participants' smartphones. Negative valence was assessed by asking, "How negative are you feeling right now?" Arousal was assessed using a composite of somatic and cognitive arousal that reverse scored and averaged two ratings, "How calm is your body?" and "How quiet is your mind?" Analyses were conducted with Bayesian general linear models using flat priors. Results: Contrary to our hypothesis, pre-sleep arousal was linearly associated with increased REM frontal theta (ß = 2.06 [0.95, 3.20], pMAP < 0.001). A quadratic association fit the data better than the linear model (Bayes Factor = 250.47), such that, for low to moderate pre-sleep arousal, REM frontal theta power increased as arousal ratings increased, but for moderate to high pre-sleep arousal, REM frontal theta power decreased as arousal ratings increased (ß = -2.04 [-3.18, -0.90], pMAP < 0.001). Both associations remained significant even adjusting for negative valence. Contrary to expectations, pre-sleep negative valence was not associated with REM frontal theta. Conclusion: Separately measuring affect dimensions revealed that REM frontal theta power was selectively responsive to naturalistic pre-sleep arousal. At higher arousal ratings, our results matched prior findings. However, at lower arousal ratings, the association was reversed, suggesting that spectral markers may vary across affective intensities and contexts. Support (If Any): National Science Foundation Graduate FellowshipR56, National Institute of Dental and Craniofacial Research, "Emotion dysregulation and sleep-time masticatory muscle activity in sleep bruxism, " DE025321